2010
DOI: 10.1089/hum.2009.157
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus-Mediated Correction of a Canine Model of Glycogen Storage Disease Type Ia

Abstract: Glycogen storage disease type Ia (GSDIa; von Gierke disease; MIM 232200) is caused by a deficiency in glucose-6-phosphatase-a. Patients with GSDIa are unable to maintain glucose homeostasis and suffer from severe hypoglycemia, hepatomegaly, hyperlipidemia, hyperuricemia, and lactic acidosis. The canine model of GSDIa is naturally occurring and recapitulates almost all aspects of the human form of disease. We investigated the potential of recombinant adeno-associated virus (rAAV) vector-based therapy to treat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 32 publications
3
84
1
Order By: Relevance
“…Both human and canine carriers for GSD-Ia maintain normal blood glucose during fasting for several hours, and do not accumulate glycogen in the liver. 1,8,9 Following a single neonatal administration of HDAd-cG6Pase vector, HDAd-treated dogs E and H with GSD-Ia had B20% of hepatic G6Pase activity observed in normal dogs (1.9 ± 0.2 mmol g -1 ), when biopsied at 7 and 22 months of age, respectively. GSD-Ia dogs that were maintained solely with diet demonstrated hepatic G6Pase activity of 0.48±0.18 mmol g -1 tissue per minute, B7% of normal's hepatic G6Pase activity ( Figure 2a).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Both human and canine carriers for GSD-Ia maintain normal blood glucose during fasting for several hours, and do not accumulate glycogen in the liver. 1,8,9 Following a single neonatal administration of HDAd-cG6Pase vector, HDAd-treated dogs E and H with GSD-Ia had B20% of hepatic G6Pase activity observed in normal dogs (1.9 ± 0.2 mmol g -1 ), when biopsied at 7 and 22 months of age, respectively. GSD-Ia dogs that were maintained solely with diet demonstrated hepatic G6Pase activity of 0.48±0.18 mmol g -1 tissue per minute, B7% of normal's hepatic G6Pase activity ( Figure 2a).…”
Section: Resultsmentioning
confidence: 98%
“…9 In contrast to the experience reported with a small genome AAV2/8 vector that could be packaged as double-stranded AAV2/8 and prolonged survival for 411 months in three consecutive dogs with GSD-Ia, Weinstein et al reported that a single-stranded AAV2/8 vector failed to prevent hypoglycemia for 42 months of age in one dog with GSD-Ia. With regard to neonatal administration of the current HDAd-cG6Pase serotype 5 vector, it performed favorably in that symptoms were prevented for 6-22 months in two consecutive dogs with GSD-Ia.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations